2009
DOI: 10.1056/nejmx090062
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Renal Support in Critically Ill Patients with Acute Kidney Injury

Abstract: BACKGROUND-The optimal intensity of renal-replacement therapy in critically ill patients with acute kidney injury is controversial.METHODS-We randomly assigned critically ill patients with acute kidney injury and failure of at least one nonrenal organ or sepsis to receive intensive or less intensive renal-replacement therapy. The primary end point was death from any cause by day 60. In both study groups, hemodynamically stable patients underwent intermittent hemodialysis, and hemodynamically unstable patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Two large randomized controlled trials, the ATN Study and the RENAL Study, both showed that more intensive RRT did not have any beneficial effects on renal recovery, nonrenal organ failure or mortality compared with less intensive RRT [62,63]. In a meta-analysis, Wang Y el at found that patients remained RRT dependent for longer while receiving higher intensity RRT(a prescribed dose of 35-48 mL/kg/h), compared with standard intensity(a prescribed dose of 20-25 mL/kg/h), in the first 28 days of treatment, which appears to delay renal recovery [64].…”
Section: Oliguria During Renal Replacement Therapymentioning
confidence: 99%
“…Two large randomized controlled trials, the ATN Study and the RENAL Study, both showed that more intensive RRT did not have any beneficial effects on renal recovery, nonrenal organ failure or mortality compared with less intensive RRT [62,63]. In a meta-analysis, Wang Y el at found that patients remained RRT dependent for longer while receiving higher intensity RRT(a prescribed dose of 35-48 mL/kg/h), compared with standard intensity(a prescribed dose of 20-25 mL/kg/h), in the first 28 days of treatment, which appears to delay renal recovery [64].…”
Section: Oliguria During Renal Replacement Therapymentioning
confidence: 99%
“…After reaching consensus on the definition of AKI by the Acute Disease Quality Initiative (ADQI) group, the AKI incidence in the general ward has been 20% [5], with rates increasing by approximately 10% per year [6]. The incidence of AKI in the intensive care unit (ICU) has been 30 to 50%, and 10% require kidney replacement therapy (KRT) [7,8]. The hospital mortality of AKI has been 27.5% in those who did not require KRT and from 33 to 53% [9] in those who required KRT.…”
Section: Introductionmentioning
confidence: 99%